PENDAMPINGAN DIVERSIFIKASI PRODUK JAHE LATTE PADA UMKM UMZA SEBAGAI UPAYA PENINGKATAN DAYA SAING PRODUK HERBAL LOKAL - M. Nur Dewi Kartikasari; Indhun Dyah Susanti; Dian Eka Ermawati; Sri Anggarini Parwatiningsih (Universitas Muhammadiyah Kudus, 2026)
This community service activity was motivated by the still low level of innovation and business legality in the herbal-based food Micro, Small, and Medium Enterprises (MSMEs) sector in the former Surakarta Residency area. The objectives of the activity were to enhance product innovation capabilities, strengthen food safety aspects through the implementation of good production practices, and support the processing of distribution permits and digital marketing strategies for UmZa MSMEs. The activity was conducted over three months in the Sukoharjo area, involving a single main partner that met the criteria for a ginger-based microenterprise. The implementation method employed a participatory approach, comprising stages of observation, focus group discussions, product diversification training, Good Manufacturing Practices training, licensing assistance, packaging innovation, and digital marketing training. The variables evaluated included increasing partner knowledge and skills, product quality, and business legality readiness. Data were collected through questionnaires, observations, and interviews, then analyzed descriptively. The results showed a 40% increase in partner knowledge, the implementation of hygienic production practices, the development of two new Jahe Latte product variants, and the preparation of distribution permit documents in accordance with regulations. This activity was concluded to have successfully increased the competitiveness and sustainability of MSMEs through the integration of product innovation, legality, and digitalization. Further mentoring is recommended to expand market reach and support halal certification for local herbal products.